Asymmetries between lower limbs during jumping in female elite athletes from the brazilian national volleyball team - Castanharo, R.; Veras Orselli, M. I.; Alcantara , C.; Miana, A.; de Jesus Manoel, E.; Proenca, J. E.; Duarte, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to assess the asymmetry during jumping between the lower limbs of female elite athletes from the Brazilian National Volleyball team. A biomechanical evaluation of two kinds of jumps (countermovement and drop) was carried out, leading to the calculation of kinetic and kinematic variables, which were related to the athletes' clinical complaints. We found important asymmetries in all athletes, and, in almost cases, it was possible to associate with their complaints. Additionally, the identified movement patterns have been described in the literature as being risky, potentially causing musculoskeletal lesions, or as indicators of a neuromuscular deficit. This investigation was useful in order to set up a physical training regime capable of minimizing asymmetries, and thus, decreasing the joint overload, aiming the prevention of injuries.